Narrative therapy : making meaning, making lives - Brown, Catrina; Augusta-Scott, Tod (Sage Publications, 2007)
Narrative Therapy: Making Meaning, Making Lives offers a comprehensive introduction to the history and theory of narrative therapy. Influenced by feminist, postmodern, and critical theory, this edited volume illustrates how we make sense of our lives and experiences by ascribing meaning through stories that arise within social conversations and culturally available discourses.